O conhecimento popular e o uso de plantas medicinais por usuários de três Unidades de Saúde da Família no interior do Estado de São Paulo/SP - Alcântara, Renata Giamlourenço Lante (2014)
Study population-territorial, transverse survey, whose general objective was to describe the popular knowledge regarding medicinal plants, along in tree Family Health Units (USF) in the State of São Paulo, in year of 2013. The specific objectives tried to report the medicinal plants used by the community, collecting their popular name (and if it was used fresh or dried household plants), the parts used, the way of preparing them, conservation, therapeutic purpose, frequency and the source for the usage. The data collection occurred through standardized interviews, there were 25 participants, indicated by USF teams. The characterization of the participants shows that the largest number are from female gender, 19 (76%) and 6 were from male gender (24%), aged between 32 and 80 years. The results reveal that the beginning of this practice, for most participants, took place from lessons with parents. Among the plants mentioned, over 100 are for medical use, characterized by some fruit, even resin and wood waste. The most cited were: guaco, mint, bilberry and ruby. Regarding the purpose of the use, the most mentioned plant is used for disorders of the respiratory tract (such as cough, sputum, rhinitis, sinusitis, influenza-like illnesses), a fact consistent with the scientific literature. It is understood that this practice contributes to enhance the recovery and preservation of cultural diversity, allowing the users to acess a better care for themselves and giving them autonomy. Thus, it is possible a revaluation of popular knowledge, aiming to recover once deleted knowledge about the way one understands life, the knowledge about the culture inherited and acquired reconciled to scientific knowledge.